Morphology and chain dynamics during collapse transition of PNIPAM gels studied by combined imaging, relaxometry and Xe-129 spectroscopy techniques - Kariyo, Sobiroh; Kuppers, Markus; Badiger, Manohar V.; Prabhakar, A.; Jagadeesh, Bharatam; Stapf, S.; Blumich, B. (Magnetic Resonance Imaging, 2005)
The temperature-induced shape transition of poly(N-isopropylacrylamide) gels of different cross-link densities was investigated by a combination of NMR techniques allowing the characterization of both the macroscopic collapse as well as the changes on a molecular scale related to the expulsion of water from the gel network. The proton-containing gel phase was visualized by swelling in heavy water, and the volume change was monitored by proton imaging for cross-link densities between 0.5 % and 2.5 %. Above the transition temperature of 35 degrees C, gel collapse led to a volume change of up to a factor of 17 for the gel of smallest cross-link density. Two spectral lines of Xe-129 are found in the gel state and are assigned to the hydrophobic and hydrophilic parts of the network. In the collapsed state, the hydrophobic peak shows a strong shift while the hydrophilic peak disappears. A considerable shortening of both T-1 and T-2 of the gel protons upon collapse was found at a field of 4.7 T. At lower fields, the effect becomes more pronounced and qualitatively different dispersion behaviors between the swollen and the collapsed states are observed. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: gel; networks; phase transition; relaxometry; Xe-129 spectroscopy

Synthetic zipper peptide motif orchestrated via co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality - Nair, Roshna V.; Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Jagadeesh, Bharatam; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2013)
Here, we report on a new class of synthetic zipper peptide which assumes its three-dimensional zipper-like structure via a co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality. Structural studies carried out in both solid- and solution-state confirmed the zipper-like structural architecture assumed by the synthetic peptide which makes use of unusually remote inter-residual hydrogen-bonding and aromatic stacking interactions to attain its shape. The effect of chirality modulation and the extent of noncovalent forces in the structure stabilization have also been comprehensively explored via single-crystal X-ray diffraction and solution-state NMR studies. The results highlight the utility of noncovalent forces in engineering complex synthetic molecules with intriguing structural architectures.

Dimedone-based rigid organic scaffold for organizing symmetrical helical peptide chains. - Madica, Krishnaprasad; Lakshmi, Jerripothula K.; Madhu, Suresh; Nadimpally, Krishna Chaitanya; Gonnade, Rajesh; Jagadeesh, Bharatam; Sanjayan, Gangadhar J. (ChemistrySelect, 2019)
We describe herein design, synthesis and conformational investigations of polypeptides attached on a rigid dimedone template. Two identical peptide chains are attached on a single carbon containing dimedone as a scaffold. Dimedone assists in controlling the secondary interactions through strong intramolecular helical C-12 and C-15 membered bifurcated hydrogen bonding on both the peptide chains along with propagating the helical architecture of the peptide chains attached. There exists a C-6 hydrogen bonding for the single stranded peptides attached to dimedone. Extensive structural investigations involving single crystal X-ray diffraction, solution-state NMR and CD studies of oligopeptides have been undertaken.
Keywords: dimedone; Helical; hydrogen bonding; Peptides; template